Pedagogical theories and the process of internalization of moral values - Juliana Santos Monteiro Vieira; Dinamara Garcia Feldens (Universidade Estadual de Maringá, 2021)
The present article proposes to reflect on the process of internalization of moral values as the primary objective of Education, through historical and philosophical sources, analyzing, for this, theoretical frameworks of Pedagogy, such as: Comenius, Pestalozzi, Herbart and Durkheim. Our methodology was based on the bibliographic and authorial writings of these theorists and we try to question the logic established in pedagogical discourses, starting from the critic of moral values formulated by Friedrich Nietzsche, emphasizing aspects present in the referred theories and their reverberations in singularities and collectivities. The process of internalizing moral values had as its priority making education an instrument for the ordering of subjects, making it useful to the interests of state culture. It is understood that subjectivities are constituted inside and outside for the moral field and that the same is not alien or should be non-existent in school. However, it has been attempted to demonstrate in this article, how the moral field has been reduced to a process of disciplining and ordering, according to pre-determined models, virtues and values, which shows the limited pedagogical perspective in the vision of the moral field, which from its conception responds to interests and prioritizes the maintenance of the status quo.